A method for preparing N-doped mesoporous carbon aerogel microspheres

By preparing N-doped mesoporous carbon aerogel microspheres, the existing carbon aerogel microspheres have solved the problems of small pore size and poor electrochemical corrosion resistance, and efficient large-scale production and low-cost carbon aerogel microsphere applications have been achieved, which significantly improves catalytic activity and stability.

CN116161642BActive Publication Date: 2025-08-12SINOSTEEL MAANSHAN INST OF MINING RES CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211568823.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-08
Publication Date
2025-08-12
Estimated Expiration
2042-12-08

AI Technical Summary

Technical Problem

When existing carbon aerogel microspheres are used as platinum carbon catalyst support, their pore size is small and not resistant to electrochemical corrosion, making them difficult to adapt to large-scale production and have high costs.

Method used

Resorcinol, resorginol, polyethylene glycol 2000 and formaldehyde were used as raw materials to prepare N-doped mesoporous carbon aerogel microspheres by emulsification method, and N-atom doping modification was used using polyethyleneimine, combined with high-temperature carbonization treatment to form high mesoporous pore size and good electrochemical corrosion resistance.

Benefits of technology

The mesoporous pore size of the prepared carbon aerogel microspheres was expanded by 5 to 8 times, and the total pore volume was increased by 2.33 times, which significantly improved catalytic activity and cyclic stability. The initial catalytic activity was 1.84 times that of commercial platinum carbon catalysts, and the activity increased to 2.3 times after 5,000 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005443261440000091
    Figure GDA0005443261440000091
  • Figure GDA0005443261440000101
    Figure GDA0005443261440000101
  • Figure GDA0005443261440000102
    Figure GDA0005443261440000102
Patent Text Reader

Abstract

The present invention discloses a method for preparing nitrogen-doped mesoporous carbon aerogel microspheres, comprising the following steps: adding resorcinol, phloroglucinol, a template agent, polyethylene glycol 2000, and formaldehyde to pure water, stirring and dissolving to obtain a precursor solution; adding the precursor solution to white oil containing a surfactant, emulsifying, and heating in an oil bath for sufficient reaction; centrifuging to obtain a powder; adding the powder and polyethyleneimine to pure water, heating in an oil bath for sufficient reaction; centrifuging to obtain a solid powder, repeatedly washing with pure water; and carbonizing to obtain nitrogen-doped carbon aerogel microspheres. The present invention uses polyethyleneimine as a nitrogen source to modify the surface of the carbon aerogel microspheres by nitrogen atom doping, thereby increasing the electron-donating capacity of the carbon in the carrier, significantly improving the cyclic stability in applications, and enhancing the electrochemical corrosion resistance of the carbon aerogel. The preparation method of the present invention has a simple preparation process, a short preparation cycle, and a low preparation cost, making it suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of porous carbon material preparation, and in particular relates to a method for preparing a mesoporous carbon aerogel, which can be used as a platinum-carbon catalyst carrier in the production of proton exchange membrane fuel cells. Background Art

[0002] Proton exchange membrane fuel cells (PEMFCs), with their high energy conversion efficiency, high power density, and pollution-free properties, have become a research hotspot in the new energy sector. However, the limited availability and high cost of Pt, the catalyst used for the cathode redox reaction, are major factors limiting the commercial application of fuel cells. Using a suitable carrier to load Pt can effectively improve its utilization and stability, thereby reducing the cost of the fuel cell stack.

[0003] Carbon aerogel, an amorphous carbon material with a tunable three-dimensional nanostructure and high surface area, porosity, and electrical conductivity, is highly suitable for platinum-carbon catalyst supports. Its high surface area facilitates the dispersion of the Pt catalyst; its rich and tunable pore structure creates an efficient three-phase reaction interface; and its high electrical conductivity facilitates electron transfer. Currently, carbon aerogels are available in three main forms: microspheres, films, and monoliths. The preparation of thin films and monoliths typically requires a lengthy solvent exchange process and complex supercritical drying, resulting in long production cycles, high costs, and limited adaptability to large-scale production. Carbon aerogel microspheres are produced through microemulsion polymerization and atmospheric pressure drying, eliminating the need for solvent exchange and supercritical drying. Their preparation process is relatively simple, with a short production cycle and low costs, and they are suitable for large-scale production. However, carbon aerogel microspheres suffer from small, difficult-to-adjust pore sizes and poor resistance to electrochemical corrosion.

[0004] Chinese invention patent CN110745807A discloses carbon aerogel microspheres and their preparation method, characterized by the ability to adjust the pore size of the carbon aerogel microspheres by controlling the amount of pore-forming agent used. The preparation process is relatively simple and adaptable to large-scale production. However, the presence of many dangling bonds on the surface of this carbon aerogel makes its electrochemical corrosion resistance less than ideal when used as a platinum-carbon catalyst carrier. Kou Shuqing et al. (National Invention Patent Publication No.: CN110474060B) disclose a method for preparing a highly efficient three-dimensional reticular nitrogen-doped carbon aerogel and its application as an oxygen reduction catalyst. This method utilizes gelatin to form a nitrogen-doped three-dimensional reticular carbon aerogel that can be obtained without activation treatment. However, the carbon aerogel prepared by this method has a small pore size, which may cause the Pt nanoparticles to be trapped in micropores that are inaccessible to the conductive polymer, preventing them from participating in the catalytic reaction, resulting in ineffective loading. Summary of the Invention

[0005] The purpose of the present invention is to address the technical difficulties of existing carbon aerogel microspheres such as small pore size and poor electrochemical corrosion resistance when used as platinum-carbon catalyst carriers, and to provide a method for preparing N-doped mesoporous carbon aerogel microspheres with high mesopore size, good electrochemical corrosion resistance, simple preparation process, short preparation cycle, low preparation cost, and adaptability to large-scale production.

[0006] To achieve the above-mentioned object of the present invention, a method for preparing N-doped mesoporous carbon aerogel microspheres of the present invention is implemented by the following steps:

[0007] (1) Preparation of precursor solution: Add resorcinol, phloroglucinol, and polyethylene glycol 2000 to a certain amount of pure water, heat and stir until completely dissolved, stop heating and continue stirring, cool to room temperature, add formaldehyde aqueous solution and stir evenly to prepare a precursor solution with a density of 0.2-0.9 g / ml.

[0008] (2) Sol-gel reaction: the precursor solution is poured into white oil containing a surfactant, emulsified using an emulsifier, and the emulsified suspension is continuously stirred while reacting in a water bath to obtain a slurry containing gel microspheres;

[0009] (3) Solid-liquid separation: The slurry is subjected to solid-liquid separation and repeated washing to obtain gel microspheres;

[0010] (4) Doping: Add the gel microspheres to a certain amount of pure water, mix them evenly with ultrasonic waves, then add polyethyleneimine and react in a water bath to obtain N-doped gel microspheres;

[0011] (5) Carbonization: The doped gel microspheres are carbonized to obtain N-doped carbon aerogel microspheres.

[0012] As a preferred embodiment of the above preparation method, in step (1), the molar ratio of resorcinol to phloroglucinol is 1:5-15, and the molar ratio of the sum of resorcinol and phloroglucinol to formaldehyde is 1:1.5-3.

[0013] As a preferred embodiment of the above preparation method, in step (1), the amount of polyethylene glycol 2000 added is 0.1% to 5% of the total mass of resorcinol, phloroglucinol and formaldehyde.

[0014] As a preferred embodiment of the above preparation method, in step (2), the surfactant is 0.5% to 1.5% of the volume of the white oil, and the volume ratio of the precursor solution to the white oil is 1:3 to 15.

[0015] Furthermore, in step (1), the heating temperature is 20-60° C.; in step (2), the stirring speed is 100-500 r / min, the water bath reaction temperature is 30-65° C., and the water bath reaction time is 6-15 h.

[0016] Furthermore, in step (4), the mass ratio of the gel microspheres to pure water is 1:10-300, and the mass ratio of the polyethyleneimine to the gel microspheres is 1:2-15.

[0017] Furthermore, in step (5), the carbonization temperature is 750-1050° C., and the carbonization time is 2-6 hours.

[0018] Through experimental research, it was found that in step (1), the molar ratio of resorcinol to phloroglucinol is preferably in the range of 1:6 to 11, and the amount of polyethylene glycol 2000 added is preferably 0.5% to 2.5% of the total mass of resorcinol, phloroglucinol and formaldehyde.

[0019] Studies have shown that in step (2), the volume ratio of the precursor solution to the white oil is preferably in the range of 1:5 to 12; in step (4), the mass ratio of the gel microspheres to pure water is preferably in the range of 1:80 to 300, and the mass ratio of the polyethyleneimine to the gel microspheres is preferably in the range of 1:5 to 15.

[0020] In order to achieve the best production efficiency and production cost, the heating temperature in step (1) is 30-60° C.; in step (2), the water bath reaction temperature is 40-60° C., and the water bath reaction time is 10-15 h.

[0021] Compared with the prior art, the preparation method of N-doped mesoporous carbon aerogel microspheres of the present invention has the following beneficial effects:

[0022] (1) The present invention uses polyethylene glycol 2000 as a template, which can produce a large number of mesoporous structures in the carbon aerogel and can also be completely decomposed into gas during the high-temperature carbonization process without the need for secondary removal.

[0023] (2) The present invention adopts the reverse microemulsion method to synthesize carbon aerogel microspheres by dispersing the precursor solution into droplets wrapped by the oil phase, which can avoid the danger of heat accumulation during large-scale synthesis.

[0024] (3) The present invention uses polyethyleneimine as a nitrogen source to perform nitrogen atom doping modification on the surface of carbon aerogel microspheres to improve the electron donating ability of carbon in the carrier, while significantly improving the cycle stability in application and enhancing the electrochemical corrosion resistance of carbon aerogel.

[0025] (4) The preparation method of the present invention has a simple preparation process, a short preparation cycle, a low preparation cost, and is suitable for large-scale production.

[0026] (5) The test results show that the particle size of the carbon aerogel microspheres prepared by the method of the present invention is mainly distributed in the range of 5 to 15 μm, the particle size distribution is reasonable, the mesopore diameter is expanded by 5 to 8 times, and the total pore volume is increased by 2.33 times.

[0027] (6) The carbon aerogel microspheres prepared by the method of the present invention can significantly improve the catalytic activity and cyclic stability of the catalyst when used as a Pt catalyst carrier. Test results show that when the Pt content is the same, the initial catalytic activity of the catalyst supported by the carbon aerogel microspheres prepared by the method of the present invention is 1.84 times that of the commercial Pt-carbon catalyst. After 5000 cycles of accelerated endurance testing, the catalytic activity is 2.3 times that of the commercial Pt-carbon catalyst, achieving unexpected technical results. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a SEM image of carbon aerogel microspheres prepared in Example 1 of the method of the present invention;

[0029] Figure 2 is an EDS image of carbon aerogel microspheres prepared in Example 1 of the method of the present invention;

[0030] Figure 3 1 is a pore size distribution diagram of carbon aerogel microspheres prepared by Example 1, Example 2, and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0031] To illustrate the present invention, the preparation method of N-doped mesoporous carbon aerogel microspheres of the present invention is further described in detail below with reference to examples. However, the present invention is not limited to the examples.

[0032] Example 1

[0033] The raw materials used to prepare the precursor in this embodiment are: resorcinol, phloroglucinol, formaldehyde, and polyethylene glycol 2000. The molar ratio of resorcinol to phloroglucinol is 8:1; the molar ratio of formaldehyde to the total amount of resorcinol and phloroglucinol is 1:1.5; and the total mass ratio of polyethylene glycol 2000 to resorcinol, phloroglucinol, and formaldehyde is 0.005:1.

[0034] Resorcinol, phloroglucinol, and polyethylene glycol 2000 were stirred and dissolved at 60° C., and then formaldehyde solution was added and continued to be stirred evenly to prepare a precursor solution with a density of 0.4 g / ml.

[0035] The precursor solution was poured into 15# white oil containing 0.5% by volume of Span 80, emulsified at low speed for 5 minutes using an emulsifier, and then poured into a three-necked flask. The suspension was reacted for 14 hours in a 50°C oil bath with stirring at 100 r / min. The volume ratio of the precursor to the white oil was 1:5.

[0036] The suspension was centrifuged and repeatedly washed with dichloromethane to obtain a powder without agglomerates. The powder was added to an aqueous solution of polyethyleneimine containing 5% by weight of the powder and reacted in a water bath at 60°C for 10 hours to obtain a turbid solution; the mass ratio of the powder to pure water was 1:80.

[0037] The turbid solution was centrifuged and washed repeatedly with pure water to obtain a powdery solid.

[0038] The powdered solid was carbonized at 850 °C for 5 h to prepare N-doped carbon aerogel microspheres.

[0039] Example 2

[0040] The raw materials used to prepare the precursor in this embodiment are: resorcinol, phloroglucinol, formaldehyde, and polyethylene glycol 2000. The molar ratio of resorcinol to phloroglucinol is 9:1; the molar ratio of formaldehyde to the total amount of resorcinol and phloroglucinol is 1:2; and the total mass ratio of polyethylene glycol 2000 to resorcinol, phloroglucinol, and formaldehyde is 0.01:1.

[0041] (1) Dissolve resorcinol, phloroglucinol, and polyethylene glycol 2000 by stirring at 50°C, then add formaldehyde solution and continue stirring to obtain a precursor solution with a density of 0.5 g / ml.

[0042] (2) The precursor solution was poured into 15# white oil containing 1% by volume of Span 80, emulsified at low speed for 5 minutes using an emulsifier, and then poured into a three-necked flask. The suspension was reacted for 14 hours in an oil bath at 50°C and stirred at 200 r / min. The volume ratio of the precursor to the white oil was 1:7.

[0043] (3) The suspension was centrifuged and repeatedly washed with dichloromethane to obtain a powder without agglomeration. The powder was added to an aqueous solution of polyethyleneimine containing 7% by mass of the powder, and the mixture was reacted in a water bath at 60°C for 12 hours to obtain a turbid solution; the mass ratio of the powder to pure water was 1:100.

[0044] (4) The turbid solution was centrifuged and washed repeatedly with pure water to obtain a powdery solid.

[0045] (5) The powdered solid was carbonized at 950 °C for 4 h to obtain N-doped carbon aerogel microspheres.

[0046] Example 3

[0047] The raw materials used to prepare the precursor in this embodiment are: resorcinol, phloroglucinol, formaldehyde, and polyethylene glycol 2000. The molar ratio of resorcinol to phloroglucinol is 10:1; the molar ratio of formaldehyde to the total amount of resorcinol and phloroglucinol is 1:2.5; and the total mass ratio of polyethylene glycol 2000 to resorcinol, phloroglucinol, and formaldehyde is 0.015:1.

[0048] (1) Dissolve resorcinol, phloroglucinol, and polyethylene glycol 2000 by stirring at 40°C, then add formaldehyde solution and continue stirring to obtain a precursor solution with a density of 0.6 g / ml.

[0049] (2) The precursor solution was poured into 15# white oil containing 1.5% by volume of Span 80, emulsified at low speed for 5 minutes using an emulsifier, and then poured into a three-necked flask. The suspension was reacted for 14 hours in an oil bath at 60°C and stirred at 300 r / min; the volume ratio of the precursor to the white oil was 1:8.

[0050] (3) The suspension was centrifuged and repeatedly washed with dichloromethane to obtain a powder without agglomeration. The powder was added to an aqueous solution of polyethyleneimine containing 10% by mass of the powder, and the mixture was reacted in a water bath at 60°C for 12 hours to obtain a turbid solution; the mass ratio of the powder to pure water was 1:150.

[0051] (4) The turbid solution was centrifuged and washed repeatedly with pure water to obtain a powdery solid.

[0052] (5) The powdered solid was carbonized at 1000 °C for 4 h to obtain N-doped carbon aerogel microspheres.

[0053] Example 4

[0054] The raw materials used to prepare the precursor in this embodiment are: resorcinol, phloroglucinol, formaldehyde, and polyethylene glycol 2000. The molar ratio of resorcinol to phloroglucinol is 11:1; the molar ratio of formaldehyde to the total amount of resorcinol and phloroglucinol is 1:3; and the total mass ratio of polyethylene glycol 2000 to resorcinol, phloroglucinol, and formaldehyde is 0.02:1.

[0055] (1) Dissolve resorcinol, phloroglucinol, and polyethylene glycol 2000 by stirring at 30°C, then add formaldehyde solution and continue stirring to obtain a precursor solution with a density of 0.7 g / ml.

[0056] (2) The precursor solution was poured into 15# white oil containing 3% by volume of Span 80, emulsified at low speed for 5 minutes using an emulsifier, and then poured into a three-necked flask. The suspension was reacted in an oil bath at 60°C for 14 hours; the volume ratio of the precursor to the white oil was 1:9.

[0057] (3) The suspension was centrifuged and repeatedly washed with dichloromethane to obtain a powder without agglomeration. The powder was added to an aqueous solution of polyethyleneimine containing 10% by mass of the powder, and the mixture was reacted in a water bath at 60°C for 12 hours to obtain a turbid solution; the mass ratio of the powder to pure water was 1:200.

[0058] (4) The turbid solution was centrifuged and washed repeatedly with pure water to obtain a powdery solid.

[0059] (5) The powdered solid was carbonized at 1000 °C for 4 h to obtain N-doped carbon aerogel microspheres.

[0060] Example 5

[0061] The raw materials used to prepare the precursor in this embodiment are: resorcinol, phloroglucinol, formaldehyde, and polyethylene glycol 2000. The molar ratio of resorcinol to phloroglucinol is 15:1; the molar ratio of formaldehyde to the total amount of resorcinol and phloroglucinol is 1:2.5; and the total mass ratio of polyethylene glycol 2000 to resorcinol, phloroglucinol, and formaldehyde is 0.02:1.

[0062] (1) Dissolve resorcinol, phloroglucinol, and polyethylene glycol 2000 by stirring at 40° C., then add formaldehyde solution and continue stirring to obtain a precursor solution with a density of 0.8 g / ml.

[0063] (2) The precursor solution was poured into 15# white oil containing 2% by volume of Span 80, emulsified at low speed for 5 minutes using an emulsifier, and then poured into a three-necked flask. The suspension was reacted in an oil bath at 60°C for 14 hours; the volume ratio of the precursor to the white oil was 1:10.

[0064] (3) The suspension was centrifuged and repeatedly washed with dichloromethane to obtain a powder without agglomeration. The powder was added to an aqueous solution of polyethyleneimine containing 30% by mass of the powder, and the mixture was reacted in a water bath at 50°C for 10 hours to obtain a turbid solution; the mass ratio of the powder to pure water was 1:250.

[0065] (4) The turbid solution was centrifuged and washed repeatedly with pure water to obtain a powdery solid.

[0066] (5) The powdered solid was carbonized at 1050 °C for 3 h to obtain N-doped carbon aerogel microspheres.

[0067] Example 6

[0068] The raw materials used to prepare the precursor in this embodiment are: resorcinol, phloroglucinol, formaldehyde, and polyethylene glycol 2000. The molar ratio of resorcinol to phloroglucinol is 5:1; the molar ratio of formaldehyde to the total amount of resorcinol and phloroglucinol is 1:3; and the total mass ratio of polyethylene glycol 2000 to resorcinol, phloroglucinol, and formaldehyde is 0.02:1.

[0069] (1) Dissolve resorcinol, phloroglucinol, and polyethylene glycol 2000 by stirring at 40° C., then add formaldehyde solution and continue stirring to obtain a precursor solution with a density of 0.8 g / ml.

[0070] (2) The precursor solution was poured into 15# white oil containing 1% by volume of Span 80, emulsified at low speed for 5 minutes using an emulsifier, and then poured into a three-necked flask. The suspension was reacted in an oil bath at 40°C for 15 hours; the volume ratio of the precursor to the white oil was 1:12.

[0071] (3) The suspension was centrifuged and repeatedly washed with dichloromethane to obtain a powder without agglomeration. The powder was added to an aqueous solution of polyethyleneimine containing 20% by mass of the powder, and the mixture was reacted in a water bath at 70°C for 10 hours to obtain a turbid solution; the mass ratio of the powder to pure water was 1:300.

[0072] (4) The turbid solution was centrifuged and washed repeatedly with pure water to obtain a powdery solid.

[0073] (5) The powdered solid was carbonized at 1050 °C for 2 h to obtain N-doped carbon aerogel microspheres.

[0074] Comparative Example 1

[0075] The preparation method of the carbon aerogel microspheres in this comparative example is the same, except that the template agent polyethylene glycol 2000 is not added to the precursor solution.

[0076] Table 1 Preparation parameters of carbon aerogel microspheres in various examples

[0077]

[0078] The above description is only a preferred embodiment of the invention and is not intended to limit the invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the invention should be included in the scope of protection of the invention.

[0079] The carbon aerogel microspheres prepared in Example 1 were scanned by electron microscope and energy spectrum scanned at the same time. The results are as follows: Figure 1 、 Figure 2 As shown. Figure 1 EDS analysis shows that N is successfully doped into the surface of carbon aerogel microspheres. Figure 2 It can be seen that the prepared carbon aerogel is a microsphere with a particle size mainly distributed in the range of 5-15 μm. At the same time, because polyethyleneimine is a polymer with an amino group on the main chain, and the molecule has both polar groups (amino groups) and non-polar groups (vinyl groups), the long polyethyleneimine chain can be well loaded on the surface of the carbon aerogel microspheres, resulting in obvious wrinkles on the surface of the carbon aerogel microspheres.

[0080] The carbon aerogel microspheres prepared in Example 1, Example 2 and Comparative Example 1 were tested for pore size. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the pore size of the carbon aerogel microspheres prepared in Example 1 without adding polyethylene glycol 2000 is mainly concentrated around 3.85 nm, while the pore size of the carbon aerogel microspheres in Example 1 and Example 2 with the addition of polyethylene glycol 2000 is mainly distributed around 20.98 and 31.59, and the mesopore diameter is expanded by 5 to 8 times.

[0081] The pore volume, specific surface area and most probable pore diameter of the carbon aerosol microspheres prepared in Examples 1-6 and Comparative Example 1 are shown in Table 2:

[0082] Table 2 Preparation parameters of carbon aerogel microspheres in various examples

[0083]

[0084] As can be seen from Table 2, the addition of polyethylene glycol not only significantly enlarges the mesopore diameter of the carbon aerogel microspheres, but also greatly increases their total pore volume. The total pore volume of the carbon aerogel microspheres prepared in Example 2 is increased by 2.33 times compared with that in Control Example 1.

[0085] The carbon aerogel microspheres prepared in Example 1 and Example 2 were loaded with Pt, and cyclic voltammetry was performed on commercial platinum-carbon catalysts with the same Pt content under the same conditions. The electrochemical active area was calculated and the results are shown in Table 3:

[0086] Table 3 Electrochemical active areas of Example 1, Example 2, and commercial platinum-carbon catalysts

[0087]

[0088] As can be seen from Table 3, after cyclic voltammetry tests and accelerated endurance tests, the catalytic activity and cycle stability of the catalyst can be greatly improved when the carbon aerogel microspheres prepared in Example 1 and Example 2 are used as Pt catalyst supports. When the Pt content is the same, the initial catalytic activity of the catalyst supported by the carbon aerogel microspheres in Example 2 is 1.84 times that of the commercial platinum-carbon catalyst. After 5000 cycles of accelerated endurance tests, the catalytic activity is 2.3 times that of the commercial platinum-carbon catalyst.

Claims

1. A method for preparing N-doped mesoporous carbon aerogel microspheres, characterized in that The following steps are involved: (1) Preparation of precursor solution: add resorcinol, phloroglucinol, and polyethylene glycol 2000 to a certain amount of pure water, heat and stir until completely dissolved, stop heating and continue stirring, cool to room temperature, add formaldehyde aqueous solution and stir evenly to form a precursor solution with a density of 0.2-0.9 g / ml; the molar ratio of resorcinol to phloroglucinol is 1:5-15, and the molar ratio of the sum of resorcinol and phloroglucinol to formaldehyde is 1:1.5-2.5; the amount of polyethylene glycol 2000 added is 0.1%-5% of the total mass of resorcinol, phloroglucinol, and formaldehyde; (2) Sol-gel reaction: the precursor solution is poured into white oil containing a surfactant, emulsified using an emulsifier, and the emulsified suspension is continuously stirred while reacting in a water bath to obtain a slurry containing gel microspheres; the surfactant is 0.5% to 1.5% by volume of the white oil, and the volume ratio of the precursor solution to the white oil is 1:3 to 15; (3) Solid-liquid separation: The slurry is subjected to solid-liquid separation and repeated washing to obtain gel microspheres; (4) Doping: Add the gel microspheres to a certain amount of pure water, mix them evenly with ultrasonic waves, then add polyethyleneimine and react in a water bath to obtain N-doped gel microspheres; the mass ratio of the gel microspheres to pure water is 1:10-300, and the mass ratio of polyethyleneimine to the gel microspheres is 1:2-15; (5) Carbonization: The doped gel microspheres are carbonized to obtain N-doped carbon aerogel microspheres.

2. The method for preparing N-doped mesoporous carbon aerogel microspheres according to claim 1, wherein: In step (1), the heating temperature is 20-60° C.; in step (2), the stirring speed is 100-500 r / min, the water bath reaction temperature is 30-65° C., and the water bath reaction time is 6-15 h.

3. The method for preparing N-doped mesoporous carbon aerogel microspheres according to claim 1 or 2, characterized in that: In step (5), the carbonization temperature is 750-1050° C., and the carbonization time is 2-6 hours.

4. The method for preparing N-doped mesoporous carbon aerogel microspheres according to claim 3, wherein: In step (1), the molar ratio of resorcinol to phloroglucinol is 1:6-11, and the amount of polyethylene glycol 2000 added is 0.5%-2.5% of the total mass of resorcinol, phloroglucinol and formaldehyde.

5. The method for preparing N-doped mesoporous carbon aerogel microspheres according to claim 4, wherein: In step (2), the volume ratio of the precursor solution to the white oil is 1:5-12; in step (4), the mass ratio of the gel microspheres to the pure water is 1:80-300, and the mass ratio of the polyethyleneimine to the gel microspheres is 1:5-15.

6. The method for preparing N-doped mesoporous carbon aerogel microspheres according to claim 5, wherein: In step (1), the heating temperature is 30-60° C.; in step (2), the water bath reaction temperature is 40-60° C., and the water bath reaction time is 10-15 h.

Citation Information

Patent Citations

  • A method for preparing a highly efficient three-dimensional network nitrogen-doped carbon aerogel and its application as an oxygen reduction catalyst.

    CN110474060B

  • Carbon aerogel microsphere and preparation method thereof

    CN110745807A